Moldovan Vocational Education and Training: Student Reports for Online Learning Experiences during the COVID-19 pandemic - Stiopca, Oleg; Cobb, Robert; Faulkner, Paula E. (European Scientific Journal, ESJ, 2021)
The COVID-19 pandemic has caused a global crisis. Many health, food, economic, transportation, and educational systems have been affected. From the most affluent to the least advantaged educational systems, K-16 and beyond are being challenged on how best to move from face-to-face to online teaching and learning. Moldova policymakers and educators are meeting to address existing educational policies needed to continue educating its student population. The purpose of this descriptive study was to assess Vocational Education and Training students’ online learning experiences during the COVID-19 pandemic. Of the 303 returned surveys, most of the participants were female (60%), studying in the platform Google Classroom and reported feeling ill-prepared for the transition from face-to-face to online learning. It was concluded that students would benefit best from online resources and adequate teacher feedback for online homework. It is recommended that a collaborative approach is employed to address the needs of students, their teachers, and parents best to navigate the learning experiences during this time of uncertainty.